Family Relationship, Moral Quotient, Coping Strategies and Psychological Well-Being of High School Students of Extra Large Sized School at Surat Thani Province - Jirangnimitsaku, Pacharapan; Wongkumsin, Theerapat (Journal of Social Sciences and Humanities Research in Asia, 2020)
The objectives of this research were: 1) to study the level of family relationship , moral quotient, coping strategies and psychological well-being of high school students, 2) to compare psychological well-being of the high school students by different personal factors, 3) to study the relationship between family relationship and psychological well-being of the high school students 4) to study the relationship between moral quotient and psychological well-being of the high school students and 5) to study the relationship between coping strategies and psychological well-being of the high school students. The samples were 363 the high school students of extra large sized school at Surat Thani Province. The data were collected by questionnaires The results as follows: 1) family relationship , moral quotient, coping strategies and psychological well-being of high school students were at rather high level, 2) the high school students had difference in the education level of the father had different psychological well-being with the statistical significance at .05 level excepted the high school students had difference in gender, class, major, GPA, year number of study at school, birth order, the education level of the mother, father’s occupation, mother’s occupation and income of the family had not different psychological well-being 3) family relationship was positively related to psychological well-being of the high school students at the statistical significance at .01 level 4) moral quotient was positively related to psychological well-being of the high school students at the statistical significance at .01 level 5) coping strategies was positively related to psychological well-being of the high school students at the statistical significance at .01 level